Downsizing the BAD BH3 peptide to small constrained α-helices with improved ligand efficiency. Issue 46 (7th November 2016) - Shepherd, Nicholas E.; Harrison, Rosemary S.; Ruiz-Gomez, Gloria; Abbenante, Giovanni; Mason, Jody M.; Fairlie, David P.
Abstract : Using macrocycles to meet the challenge of reducing proteins to smaller molecules that maintain affinity and inhibitory potency for Bcl-xL. Abstract : Bcl2 Homology (BH) proteins can either trigger or prevent programmed cell death or apoptosis. Deregulation of the BH protein family network leads to evasion of apoptosis, uncontrolled proliferation and is a hallmark of cancer. Inhibition of pro-survival BH proteins is a promising chemotherapeutic strategy for certain cancers. We have examined whether helix-constrained peptides based on the BAD BH3 domain (residues 103–127) can be downsized to much smaller more drug-like peptides. We report the preparation, structural characterisation, in vitro Bcl-xL inhibition and leukemic T-cell killing ability of 45 linear, mono-, bi- and tricyclic helical peptidomimetics between 8- and 19-residues in length. We show that the BAD BH3 can be downsized to 8–14 residues and still maintain appreciable affinity for Bcl-xL. In addition, the binding efficiency indices (BEI) of the downsized mimetics are significantly higher than the BAD BH3 and similar stapled BH3 mimetics, approaching drug-like molecules. This suggests that bicyclic and monocyclic mimetics based on BH3 domains are much more efficient binding ligands than the longer peptides which they mimic.